52.2k views
3 votes
If 3(n-2)=6 , then what does n-2/n+2

1 Answer

4 votes

Answer:


(1)/(3)

Explanations:

Given the expression 3(n-2) = 6

First, we need to get the value of 'n' from this equation:


\begin{gathered} 3(n-2)=6 \\ 3n-6=6 \\ 3n=6+6 \\ 3n=12 \\ n=(12)/(3) \\ n=4 \end{gathered}

Next is to get the value of the expression n-2/n+2.

Substitute n = 4 into the expression we are looking for as shown:


\begin{gathered} (n-2)/(n+2)=(4-2)/(4+2) \\ =(2)/(6) \\ =(1)/(3) \end{gathered}

This shows that the value of n-2/n+2 is 1/3

User JBlake
by
5.1k points